The Role of Marketing Communication Strategy in Building Brand Loyalty at Fellas Organizer - Rahman, Rahman; Umam, Choerul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
In the highly competitive wedding organizer industry, building long-term customer relationships through effective communication is essential for maintaining a sustainable business. Fellas Organizer, as a premium service provider, requires a strategic approach to maintain its market position and customer commitment. This study aims to analyze the influence of Marketing Communication Strategy, which includes Advertising, Public Relations, Direct Marketing, and Sales Promotion, on Brand Loyalty at Fellas Organizer. This research employs an explanatory quantitative method with a sample of 111 respondents selected through a non-probability sampling technique. Data were analyzed using Partial Least Square Structural Equation Modeling (PLS SEM) with SmartPLS 4 software to ensure robust statistical results. The empirical findings reveal that the Marketing Communication Strategy variables explain 87.8% (R2 = 0.878) of the variance in Brand Loyalty, indicating a very strong predictive power. Partially, the hypothesis testing proves that Advertising and Direct Marketing have a positive and significant effect on Brand Loyalty, suggesting that visual engagement and personalized interactions are the primary drivers of loyalty. Conversely, Public Relations has no significant impact, while Sales Promotion demonstrates a significant negative influence. These results indicate that for a premium service provider, price-based promotions may be perceived to diminish the brand’s exclusivity and value. Fellas Organizer is advised to prioritize value-added strategies and maintain its premium positioning to ensure long-term brand loyalty.